La Littérature Musicale Congolaise: La Fête Des Mots - Yoka, Lye M. (Afrika Focus, 2019)
Much has been written on modern Congolese music, particularly in terms of its history and sociology. However, there are no studies dedicated to the literary qualities of the song texts in stylistic, paremiological and thematic terms. In addition, when considering this body of music, the tenacious survival of oral traditions should be taken into account. Such traditions take in the vivid culture of the “eristic”, the art of dispute and energetic discussion, accompanied by satirical turns and more or less subversive circumlocutions. Finally, assert that what “purist” critics consider as “para-literature” (a rather deprecating term) is literature both in terms of its thematic and formal concerns. KEYWORDS: MUSICAL LITERATURE, ODYSSEY AND EPIC OF THE CONGOLESE RUMBA, TRANSPHRASTIC AND SYNTAGMATIC CHARACTERS, DISGUISE OF THEMATIC PROFFERED, PAREMIOLOGICAL REINVENTIONS